McMasters - Morgan, Lee (New York Jove Books, 1995)
Color illustration on front cover of man in purple shirt, turqoise bandana and white hat holding rifle while standing on rock. Behind his head superimposed gold badge reading "Cattleman Association." In background red storm clouds and bolts of lightning with woman in blue dress riding horse through desert landscape.
Keywords: Western stories